Kinetics of P - Nitrophenyl Acetate Hydrolysis Catalyzed by ?- Chymotrypsin in Presence of Polyethylene Glycol - Lissi-Gervaso, E; Abuin-Saccomano, E (2011)
The effect of poly (ethyleneglycol) (PEG) addition on the rate of p-nitrophenyl acetate (PNPA) catalyzed by a- chymotrypsin has been measured in TRIS buffer at pH = 7.4. The presence of PEG (up to 30 % p/v) leads to an increase in the rate of the process. The effect of PEG is evident both, in the pre-steady state and steady state stages of the process. The reaction follows a Michaelis-Menten mechanism under all the conditions employed. The Michaelis constant slightly decreases and the catalytic rate constant slightly increases with PEG concentration over all the polymer concentration range employed (up to 30%). The decrease in the Michaelis constant suggests that the effect of the polymer is due to crowding.